Impact of Release Intervals and Densities of Trichogramma chilonis (Ishii) (Hymenoptera: Trichogrammatidae) Against the Sugarcane Stem Borer, Chilo infuscatellus (Lepidoptera; Pyralidae) under Field Conditions - Raza Muhammad; Maqsood Anwar Rustamani; Nazia Suleman; Nazir Ahmad; Qadeer Ahmad (Journal of Basic & Applied Sciences, 2021)
The parasitization of Trichogramma chilonis parasitoids was found higher in the blocks where parasitoids were released to control Chilo infuscatellus at weekly interval (52.4 %) as compared to fortnight (40.9%) and monthly intervals (32.7%). Mean parasitization was (42.7%) when 80,000 thousand parasitoids were released on monthly basis followed by 41.4% (40,000), 37.8% (20,000) and 34.0% (10,000). However the mean infestation was below economic threshold levels ranging from 5.3 to 6.5 % in all the blocks where the parasitoids were released in variable numbers.